2022
DOI: 10.1002/ejp.2025
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid treatment in patients with complex regional pain syndrome: A systematic review

Abstract: Background and objective The pathophysiology of complex regional pain syndrome (CRPS) is multifactorial, with an exaggerated inflammatory response being the most prominent. Treatment for CRPS is carried out according to the presenting pathophysiological mechanism. Anti‐inflammatory treatment with glucocorticoids is therefore an option. The aim of this study was to systematically review the efficacy of glucocorticoids in CRPS. Databases and data treatment Embase, Medline, Web of Science and Google Scholar were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Journal of Pain Research 2023:16 https://doi.org/10.2147/JPR.S423733 DovePress 3063 serum. 50,52,54,55 The elevated levels of TNF-α and IL-6 in the skin of CRPS patients persist throughout both acute and chronic stages, indicating a persistent role for cytokines in exacerbating neurogenic inflammation of CRPS. 56 Animal studies have yielded similar findings, as demonstrated by a significant upregulation of proinflammatory mediators and chemokines in the plantar, spinal dorsal horn (SDH), and DRG of rats in the chronic post-ischemia pain (CPIP) model of CRPS.…”
Section: Cytokinesmentioning
confidence: 99%
“…Journal of Pain Research 2023:16 https://doi.org/10.2147/JPR.S423733 DovePress 3063 serum. 50,52,54,55 The elevated levels of TNF-α and IL-6 in the skin of CRPS patients persist throughout both acute and chronic stages, indicating a persistent role for cytokines in exacerbating neurogenic inflammation of CRPS. 56 Animal studies have yielded similar findings, as demonstrated by a significant upregulation of proinflammatory mediators and chemokines in the plantar, spinal dorsal horn (SDH), and DRG of rats in the chronic post-ischemia pain (CPIP) model of CRPS.…”
Section: Cytokinesmentioning
confidence: 99%
“…12,13 A recent review showed corticoid treatment to be successful in treating CRPS, especially regarding pain relief and improvement in range of motion. 14 However, the optimal route of administration and optimal dose are still unknown. Today, in our clinic, a standardized moderate dose regimen is conducted in patients with clinical signs of inflammation and an elevated sIL-2R level.…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…A recent review showed corticoid treatment to be successful in treating CRPS, especially regarding pain relief and improvement in range of motion 14 . However, the optimal route of administration and optimal dose are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review exhibited corticoid treatment to be effective in CRPS, especially concerning pain relief and improved movement. 12 However, longer duration of corticoid treatment is associated with a high risk of side effects. 13 Alternative treatment options are therefore necessary.…”
Section: Introductionmentioning
confidence: 99%